PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGAJARKAN NILAI-NILAI MORAL AGAMIS DI SMPN 1 KWANYAR BANGKALAN MADURA - Wardatud Dihniyah; Syamsuddin Syamsuddin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
In the context of teaching religious moral principles at SMPN 1 Kwanyar, Bangkalan, Madura, the purpose of this study is to investigate the role that teachers of Islamic Religious Education (PAI) play in the process. In order to collect data, the method that was utilized was a qualitative approach with a case study design. The tools that were utilized for data collection included interviews, observations, and documentation. In addition to this, the research is centered on determining the elements that either promote or limit the success of PAI teachers in teaching moral principles in their students. According to the findings, PAI teachers play a significant part in molding the personalities of their pupils. This takes place not only through the dissemination of religious content, but also through the demonstration of exemplary behavior, mentorship, and learning strategies that involve interaction. The PAI teachers at this school use lectures, discussions, and storytelling methods to internalize moral values and are actively involved in religious extracurricular activities. Despite challenges such as the negative influence of social media, PAI teachers strive to overcome them by designing relevant and creative programs. In conclusion, PAI teachers at SMPN 1 Kwanyar, Bangkalan, Madura, play an effective role in teaching religious moral values, although several obstacles still need to be addressed to strengthen students’ character and moral education.